Mortality Patterns of Toxoplasmosis and Its Comorbidities in Tanzania: A 10-Year Retrospective Hospital-Based Survey - Mboera, Leonard E. G.; Kishamawe, Coleman; Kimario, Evord; Rumisha, Susan F. (Frontiers in Public Health, 2019)
Introduction: Toxoplasmosis is a parasitic zoonosis and an important cause of abortions, mental retardation, encephalitis, blindness, and death worldwide. Few studies have quantified toxoplasmosis mortality and associated medical conditions in Sub-Saharan Africa. This retrospective hospital-based study aimed to determine the mortality patterns of toxoplasmosis and its comorbidities among in-patients in Tanzania. Methods: Data on causes of death were collected using customized paper-based collection tools. Sources of data included death registers, inpatient registers and International Classification of Diseases report forms. All death events from January 2006 to December 2015 were collected. Data used in this study is a subset of deaths where the underlying cause of death was toxoplasmosis. Data was analysed by STATA programme version 13. Results: Thirty-seven public hospitals were involved in the study. A total of 188 deaths due to toxoplasmosis were reported during the 10-year period. Toxoplasmosis deaths accounted for 0.08% (188/247,976) of the total deaths recorded. The age-standardised mortality rate per 100,000 population increased from 0.11 in 2006 to 0.79 in 2015. Most deaths due to toxoplasmosis affected the adult age category. Of the 188 deaths, males accounted for 51.1% while females for 48.9% of the deaths. Dar es Salaam, Mbeya, Pwani, Tanga, and Mwanza contributed to over half (59.05%) of all deaths due to Toxoplasmosis. Of the total deaths due to toxoplasmosis, 70.7% were associated with other medical conditions; which included HIV/AIDS (52.6%), HIV/AIDS+Cryptococcal meningitis (18.8%) and HIV+Pneumocystis pneumonia (6.8%). Conclusion: The age-standardised mortality rate due to toxoplasmosis has been increasing substantially between 2006 and 2015. Most deaths due to toxoplasmosis affected the adult age category and were highly associated with HIV/AIDS. Appropriate interventions are needed to alleviate the burden of toxoplasmosis in Tanzania.